Faktor Kepuasan Kerja dan Motivasi Sebagai Dampak dari Kinerja Pegawai Dalam Penggunaan Absensi Digital. - Jumarpati, Jumarpati; Nurhayati, Nurhayati; Auralia Mujahida, Siti Rahma Kumala Dewi, (YUME : Journal of Management, 2024)
Employee performance is a result achieved by the employee in his work according to certain criteria that apply to a particular work. The success or failure of employee performance achieved by the organization will be influenced by the level of performance of employees individually and in groups. From the results of research conducted by (Suwardi & Utomo, 2011) organizationally, employees with low commitment will have an impact on turnover, high absenteeism and increased work inertia. Thus, low levels of employee absenteeism or presence will directly affect work results. This research aimed to find out how work satisfaction and motivation influence employee performance at Inspectorate Office of Palopo Regency Government. This research was a quantitative research that investigated the influence between variables, namely the independent variable and the dependent variable by proposing a hypothesis. The population used in this research was 165 respondents and was also used as a sample (saturated sample). The analytical tool was multiple linear regression analysis, data validity testing (t test and f test) using the SPSS version 21 for Windows program. Primary data was obtained from questionnaires. The questionnaire was measured using a Likert Scale which was tested for validity and reliability. The research results based on validity and reliability tests show that the data is valid (< 0.005) and reliable (> 0.06). Based on the t test and f test, it shows that work satisfaction (-0.019) partially has no effect on employee performance at Inspectorate Office of Palopo Regency Government, motivation (0.564) partially has an effect on employee performance in the General and Protocol Section of the Palopo Regency Regional Secretariat. Meanwhile, the f test simultaneously shows a significant relationship (0.030) between work satisfaction and motivation variables on employee performance at Inspectorate Office of Palopo Regency Government.Keywords: work satisfaction, motivation, employee performance